Evaluation of acrylic acid-co-acrylamide ratio on swelling kinetics and diffusion behavior - Suriati, Ghazali; Wei, Jian Goh; Siti Nur Ainda, Mazlan; Syarifah, Abd Rahim; Saidatul Shima, Jamari (ICE Publishing, 2021)
The present study aims to evaluate the effect of the monomer-to-comonomer ratio (1.00, 1.25, 1.50, 1.75, 2.00) on the swelling kinetics and diffusion behavior of a hydrogel. In this study, hydrogels with different ratios were prepared by inverse suspension polymerization using acrylic acid (AA) as the monomer and acrylamide (AM) as the comonomer with a fixed amount of AM. The chemical, morphological and thermal properties of the hydrogels were also analyzed. Swelling analyses showed that the hydrogels followed second-order swelling kinetics, while for the diffusion behavior, the hydrogels obeyed Fickian diffusion with n values less than 0.5. Hydrogel_1.5 showed the lowest n value with the presence of strong broad O–H stretching for carboxylic acid. The thermogravimetric analysis showed that Hydrogel_1.5 had the highest thermal stability compared with other ratios. In conclusion, Hydrogel_1.5 is a potential starting ratio for AA-co-AM hydrogel by inverse suspension polymerization for future development.